The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4067/s0717-95022014000200026
|View full text |Cite
|
Sign up to set email alerts
|

Dental Pulp Fibroblast and Sex Determination in Controlled Burial Conditions

Abstract: SANDOVAL, C.; NUÑEZ, M. & ROA, I.Dental pulp fibroblast and sex determination in controlled burial conditions. Int. J. Morphol., 32(2):537-541, 2014. SUMMARY:The need to identify bodies that are found as a result of disappearances with a diversity of causes, illegal burials and massive disasters, represent a wide percentage of dentistry practice on forensic research. The following study determined the performance of Barr Body Test, in fibroblasts of healthy teeth, under different conditions of burial (in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…accuracy by Papanicolaou stain [28,29]. In another study on buccal smears, methylene blue showed 88% accuracy, and H&E showed 80% accuracy [30].…”
Section: Discussionmentioning
confidence: 99%
“…accuracy by Papanicolaou stain [28,29]. In another study on buccal smears, methylene blue showed 88% accuracy, and H&E showed 80% accuracy [30].…”
Section: Discussionmentioning
confidence: 99%
“…Hence the quantity of the pulp tissue was less compared to that usually retrieved from the permanent teeth. 9 However, many studies have shown that it is possible to determine the gender of an individual even if the quantity of DNA obtained from the pulp tissue was as less as 20-70 pg of good quality DNA. 10 According to Jacqueline B.…”
Section: Discussionmentioning
confidence: 99%